Svetlyi put' . The Radiant Path - Aleksandrov, Grigori (Mosfilm, 1940)
Comedy. In the 1930s, illiterate peasant girl Tatiana Morozova works as a maid in a provincial town. As she begins to study her master fires her. But the girl does not give up her studies; she goes to work at a textile factory, becomes an exemplary shock worker, and is finally elected as a deputy to the Supreme Soviet.